Another smoking hazard: raised serum IgE concentration and increased risk of occupational allergy. Issue 6301 (7th November 1981) - Zetterström, O; Osterman, K; Machado, L; Johansson, S G
Abstract : Individual smoking histories of a general population sample and of two groups of workers exposed to occupational allergens were related to serum IgE concentrations and results of radioallergosorbent and prick tests in the workers. The geometric mean IgE concentration was higher in smokers than in non-smokers. The distribution of serum IgE values in the two groups showed an apparent difference, with a bimodal appearance in the smokers. Evidence of sensitisation against occupational allergens was more common in workers who smoked. The adjuvant effect of smoking on IgE antibody production might be due to damage to airways mucosa and supports the mucosal theory of atopy.